Heat Transfer in Engineering - Lee, Moo-Yeon; Seo, Jae-Hyeong (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The advancements in research related to heat transfer has gathered much attention in recent decades following the quest for efficient thermal systems, interdisciplinary studies involving heat transfer, and energy research. Heat transfer, a fundamental transport phenomenon, has been considered one of the critical aspects for the development and advancement of many modern applications, including cooling, thermal systems which contain symmetry analysis, energy conservation and storage, and symmetry-preserving discretization of heat transfer in a complex turbulent flow. The objective of this book is to present recent advances, as well as up-to-date progress in all areas of heat transfer in engineering and its influence on emerging technologies.